Unusual stabilization of larger acenes and heteroacenes - Müller, Matthias; Ahrens, Lukas; Brosius, Victor; Freudenberg, Jan; Bunz, Uwe H. F. (Journal of materials chemistry. C, Materials for optical and electronic devices, 2019)
The larger acenes and heteroacenes (>pentacenes) are attractive, yet sensitive materials; several strategies were developed to stabilize such species. “Classic” approaches employ bulky substituents that also solubilize these polycyclic aromatic (aza)hydrocarbons. Alternative strategies were developed conferring kinetic stabilization through solid state arrangements, addition of further Clar sextets through π-extension, on-surface syntheses and stabilization through extreme steric shielding, giving a highly twisted acene backbone. Another option is the generation of isoelectronic acene analogues from π-extended quinodimethanes. Some of the highly stabilized materials do not mimic the characteristics of their parent (aza)acenes but exhibit different - yet attractive - properties, dissected in this review.